Vatican II and beyond : the changing mission and identity of Canadian women religious - Bruno-Jofré, Rosa del Carmen, 1946-; MacDonald, Heidi; Smyth, Elizabeth M. (Elizabeth Marian), 1954- (McGill-Queen's University Press, 2017)
A look at the impact of Vatican II through the Canadian Religious Conference and the lived experience of Sisters Alice Trudeau and Mary Alban.